TRANSFORMATIONS OF CIVIL AVIATION IN UKRAINE IN THE 21ST CENTURY - Grebennikov Vоlodymyr; Smolnikov, Yuri (Proceedings of National Aviation University (archive), 2019)
Formulation of the problem. The Civil Aviation of Ukraine plays a significant role in the Ukrainian society and in the international arena. It performs multifaceted functions - passenger and cargo transportation, conducting aviation works in agrarian and forestry farms, providing medical aid, performing search and rescue operations, fire fighting, construction works, cultural and sporting events, scientific research, etc. Currently, an objective study of the aviation industry is relevant, especially since there are some problems that create a negative impression of Ukrainian aviation and the perception of its decline in modern conditions. Goal. To analyze the activity of civil aviation of Ukraine from the beginning of the 21st century to the present and, using the problem-chronological method, to comprehensively investigate the processes of transformation in the aviation industry by its main functional directions and to identify their characteristic features, focusing on the integration of Ukrainian aviation into the European and world aviation space, air traffic trends, innovations in the development of airports and airlines, problems of aircraft construction of different types of aircraft and unmanned aerial vehicles, training aircraft specialists in modern conditions. Results: The new 21st century was also a new stage in the development of civil aviation in Ukraine, which, thanks to the transformations, was characterized by a positive dynamics of its growth. Basically there was a consistent process of integration of domestic aviation into international aviation organizations, the standards and recommended practices of ICAO were being more actively implemented, and air transportation was growing. Innovations in aviation and industrial infrastructure were applied, attention was focused on the problems of aviation safety and flight safety, scientific and technical developments; measures were taken to solve global problems, such as improving the level of environmental friendliness of aviation transport, the quality of training of aviation specialists and the like. However, the strong potential in all areas of the aviation industry is not suffiently used for a variety of external and internal reasons, and solving existing problems will contribute to the sustainable development of both the aviation industry, the economy of Ukraine and international cooperation.